FORAGE IDENTIFICATION IN PADDY RICE FIELD, PANDAWAI DISTRICT, EAST SUMBA REGENCY - Hambakodu, Marselinus; Wadu, Junaedin (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak, 2022)
Forage in rice fields needs to be recorded and managed because it’s a source of cheap and easily obtained feed for livestock consumption. The problem in conducting the experiment in rice fields that there was no data information of the plant types that were used as forage for ruminant livestock. This study aims to identify forages grown in the rice fields of Pandawai District, East Sumba Regency. The research used survey methods, direct observation, and direct measurements in the field. Forage identify done by using the species identification sheet by matching the plants and compared to PlanNet apps. The results showed that the paddy field area of Pandawai District, East Sumba Regency had 10 grass species were Leersia hexandra, Cyperus sphalelatus, Leptochioa filiformis, Imperata cylindrica, Echinochios colona, Eragrotis unioloides, Cyperus Iria L., Setaria palide, Panicum repens, and Eragrotis spp. 7 leguminous species were Pueraria phaseoloides, Siratro, Sesbania bispinosa, Chamaecrista mimosoides (L)., Nila, Desmodium desv., and Desmodium sp. 5 weed species were Ludwigia otctovalvis, Stylosanthes, Phyliantus minuri, Mikania micranta and Euphorbia hirta. The type of forage that dominates the rice fields was grass 71,24%, followed by legumes 17,79%, and weeds 10,97%. The most dominant species of grass was Leersia hexaandra. Key words: botanical composition, forages, rice field